Neuroprotective Effect of Morinda citrifolia on Behavioural and Biochemical Deficits in PTZ-induced Kindled Mice - Ali, Moazzam; Singh, Prabhat; Singh, Lubhan; Pandey, Rupesh K.; Soni, Priyadarshini; Singh, Akansha (Infectious Disorders - Drug Targets, 2023)
Introduction: Epilepsy is a group of chronic neurological disorders characterized by seizures. Kindling, a chronic epileptic mouse model, was used to explore the epileptogenic mechanism and seek new anti-epileptics. In kindling, sub-convulsive (chemical/ electrical) stimuli were delivered repeatedly and erratically, eventually causing massive convulsions. Moreover, Morinda citrifolia (Noni) extracts are used as a remedy in ayurvedic preparations for many ailments. Noni has recently been shown to protect mice from amyloid beta-induced memory loss. Objective: This study was used to investigate the neuroprotective potential of Morinda citrifolia in mice over pentylenetetrazol (PTZ)-induced kindling seizure. Methods: Kindling was provoked by subsequent (one-day-gap) injections of PTZ (subconvulsive; 35 mg/kg; s.c.) for 29 days in mice. Following PTZ injection, convulsive behaviours were noted for 30 minutes. Forced swimming test (depressive behaviors), elevated plus-maze, and passive avoidance tests were employed to evaluate cognition. Brain homogenate was used to estimate oxidative stress (glutathione, superoxide-dismutase, lipid-peroxidation) and acetylcholinesterase activity. Results: PTZ-provoked kindled mice displayed depressive behaviors, impaired locomotion, cognitive dysfunctions and various biochemical changes. However, treatment with Morinda citrifolia extract (500 and 1000 mg/kg, p.o) and valproic acid (200 mg/kg, p.o) before 60 min of each PTZ injection diminished kindling scores and restored behavioural, and biochemical changes. Conclusion: Our findings suggest Morinda citrifolia offered neuroprotective effects against PTZinduced kindling seizures in mice, which were established by behavioural and biochemical paradigms.
Keywords: Morinda citrifolia